In Vitro Activity of Ceftaroline against Staphylococcus aureus Isolates Collected in 2012 from Latin American Countries as Part of the AWARE Surveillance Program - Biedenbach, Douglas J. (Antimicrob Agents Chemother, 2015)
The in vitro activities of ceftaroline and comparators, using broth microdilution, were determined against 1,066 Staphylococcus aureus isolates from hospitalized patients. Seventeen medical centers from Latin American countries contributed isolates. Methicillin-resistant S. aureus (MRSA) percentages ranged from 46% (Brazil) to 62% (Argentina). All methicillin-susceptible S. aureus (MSSA) isolates were susceptible to ceftaroline. Ceftaroline activity against MRSA varied with MIC(90)s of 0.5 (Venezuela) to 2 (Brazil, Chile, and Colombia) μg/ml, which was the highest MIC value. ST-5 was the most common sequence type.